Lower redemption of monthly Special Supplemental Nutrition Program for Women, Infants and Children benefits associated with higher risk of program discontinuation - Christopher E Anderson; Catherine E Yepez; Shannon E Whaley (Cambridge University Press, 2023)
Abstract Objective: To determine whether Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) food benefit redemption is associated with discontinuing WIC participation, failure to recertify, overall and by race/ethnicity-language preference and participant category. Design: Retrospective cohort study, using multivariable modified Poisson regression to determine risk ratios (RR) and 95 % CI for associations between household-level food benefit redemption (interval-scaled benefit redemption percent, averaged across WIC benefit subcategories, for the final 3, 6 and 12 months of certification) and failure to recertify in WIC, overall and within strata of race/ethnicity-language preference and participant category. Setting: WIC administrative data collected November 2019-July 2021 in Southern California. Participants: WIC-participating children ages 0-3 years at initial certification from November 2019 to May 2020 (n 41 263). Results: In all time periods, and for all subgroups, every 10 % lower food benefit redemption was associated with increased risk of failure to recertify. Among households without missing food benefit data, failure to recertify risk peaked at 505 % higher (RR = 6·05, 95 % CI (5·63, 6·51)) in households with average 12-month redemption <10 % compared with households with ≥70 % redemption. Conclusions: Lower WIC benefit redemption was associated with higher risk of failing to recertify among participants. Focused nutrition education around benefit redemption may improve WIC retention and child health through incremental increases in food benefit redemption.